Development of a modified Hardy-Cross algorithm for time-dependent simulations of water distribution networks - Demir, Selami; Yetilmezsoy, Kaan; Manav, Neslihan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2008)
The Hardy-Cross method that has been widely used in steady-state analyses of water distribution networks was Modified in this study. The modified methodology involves the steady-state solutions of the system at various instants. The methodology suggests bringing these stead-state solutions together to form a time-dependent simulation result. A spreadsheet solution was also developed for the modified Hardy-Cross algorithm. Microsoft Excel (TM) macros were used to implement the newly developed algorithm. The computer program is able to perform both steady-state and time-dependent analyses. It offers the use of Darcy-Weisbach or Hazen-Williams equations for the calculation of frictional losses. Both Jain and Colebrook-White equations can be used in the analyses. The computer program can also account for minor losses through the pressure pipes. The program was tested for an example water distribution system along with EPANET calculations. The modified Hardy-Cross method was proved to be an accurate tool for time-dependent simulation of water distribution networks. This study represents the development of this accurate, modified algorithm based on steady-state Hardy-Cross Method. This newly developed methodology can easily be used for both educational and professional purposes.
Keywords: Hardy-Cross; water distribution system; steady-state; time-dependent simulation; Environmental Sciences & Ecology